DEVELOPMENT OF CONSTITUTIONAL LAW IN INDONESIA - Zainuddin, Zainuddin (Proceeding International Seminar of Islamic Studies, 2023)
The term constitutional law is also commonly used in the legal lecture literature, where it is known as the term state law, which in fact both terms are translations of the Dutch term staatsrecht. The development of constitutional law in Indonesia starts from customary HTN. During the reign of the Dutch East Indies, the HTN of the Dutch East Indies was in force. When the Japanese occupied Indonesia, what applied was the HTN during the Occupation of the Japanese Army. After Indonesia was proclaimed its independence on August 17, 1945, what took effect was HTN Indonesia (Initial Period of Independence - Validity of the 1945 Constitution in the Republic of Indonesia which was one of the states within the RIS Country - Period of Validity of the 1950 Constitution - Old Order Period - New Order Period - Period Reform Order). The demand for changes in the representation system was followed by the emergence of debates about the general election system (for example between districts or proportional, between open and closed list systems) and parliamentary structure (for example the problem of parliamentary chambers and the existence of the DPD). The demand for a more equitable relationship between the center and the regions is followed by theoretical studies on the form of the state and models for implementing regional autonomy. These demands cover many aspects. The existing regulatory and institutional framework according to the positive Constitutional Law at that time was no longer in accordance with the development of people's aspirations and life.